Stable isotope paleoecology of Late Pleistocene Middle Stone Age humans from the Lake Victoria basin, Kenya. Issue 82 (May 2015) - Garrett, Nicole D.; Fox, David L.; McNulty, Kieran P.; Faith, J. Tyler; Peppe, Daniel J.; Van Plantinga, Alex; Tryon, Christian A.
Abstract: Paleoanthropologists have long argued that environmental pressures played a key role in human evolution. However, our understanding of how these pressures mediated the behavioral and biological diversity of early modern humans and their migration patterns within and out of Africa is limited by a lack of archaeological evidence associated with detailed paleoenvironmental data. Here, we present the first stable isotopic data from paleosols and fauna associated with Middle Stone Age (MSA) sites in East Africa. Late Pleistocene (∼100–45 ka, thousands of years ago) sediments on Rusinga and Mfangano Islands in eastern Lake Victoria (Kenya) preserve a taxonomically diverse, non-analog faunal community associated with MSA artifacts. We analyzed the stable carbon and oxygen isotope composition of paleosol carbonate and organic matter and fossil mammalian tooth enamel, including the first analyses for several extinct bovids such as Rusingoryx atopocranion, Damaliscus hypsodon, and an unnamed impala species. Both paleosol carbonate and organic matter data suggest that local habitats associated with human activities were primarily riverine woodland ecosystems. However, mammalian tooth enamel data indicate that most large-bodied mammals consumed a predominantly C4 diet, suggesting an extensive C4 grassland surrounding these riverine woodlands in the region at the time. These data are consistent with other lines of paleoenvironmental evidence that imply a substantially reduced Lake Victoria at this time, and demonstrate that C4 grasslands were significantly expanded into equatorial Africa compared with their present distribution, which could have facilitated dispersal of human populations and other biotic communities. Our results indicate that early populations of Homo sapiens from the Lake Victoria region exploited locally wooded and well-watered habitats within a larger grassland ecosystem.